Thermally cross-linked fluorescent materials based on vinyl groups and their applications

By using vinyl group-based thermal crosslinked fluorescent materials in the luminescent layer materials of OLED devices, the energy level difference of molecules is adjusted, and efficient yellow light emission and excellent organic electroluminescent device performance are achieved, and the existing technology is solved Inadequate preparation of medium luminescent layer materials.

CN116478137BActive Publication Date: 2025-02-25JIANGSU YONGYAN NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310357391.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-06
Publication Date
2025-02-25
Estimated Expiration
2043-04-06

AI Technical Summary

Technical Problem

In existing OLED devices, the preparation of luminescent layer materials is mainly concentrated on hole transport materials and electron transport materials. There is little research on direct modification on luminescent layer materials, resulting in insufficient luminescent performance and stability.

Method used

Using a heat-crosslinked fluorescent material based on vinyl groups, the host material is constructed by 3-vinyl carbazole and 3,3'-bipyridine, and the guest material is constructed by 4-vinyl dianiline and bis(phenylsulfonyl)benzene. , adjust the energy level difference between the singlet state and triplet state of the molecule to achieve efficient TADF materials.

Benefits of technology

The high-efficiency yellow light emission performance was achieved, excellent organic electroluminescent device performance was obtained, and a light-emitting layer with anti-solvent and thermal stability was formed through cross-linking reaction, which solved the upper solvent on the lower film when the multi-layer solution method was prepared. Corrosion problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0004163778600000031
    Figure BDA0004163778600000031
Patent Text Reader

Abstract

The present invention belongs to the technical field of organic electroluminescent materials, and specifically discloses a thermally cross-linked fluorescent material based on vinyl groups and its application. In the molecular design of the thermally cross-linked heat-activated delayed fluorescent material, bis(phenylsulfonyl)benzene and 3,3'-bipyridine groups are introduced as molecular skeletons, 4-vinyl diphenylamine and 3-vinyl carbazole are used as electron-donating groups, and ethylene is used as a cross-linking group and molecular construction is performed. Cross-linking groups are introduced into the molecules, and a three-dimensional network polymer is formed after cross-linking. After cross-linking, the light-emitting layer has the characteristics of anti-solvent and thermal stability, which can avoid the light-emitting layer from being mutually dissolved with other layers, so that the light-emitting layer of OLED can be prepared by solution processing, which is of great significance to solving the corrosion problem of the upper layer solvent on the lower layer film when preparing by the multilayer solution method, and is conducive to the industrial production of large-scale OLED device preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic electroluminescent materials, and particularly relates to a thermally cross-linked fluorescent material based on vinyl groups and application thereof. Background Art

[0002] Organic Light-Emitting Diode (OLED) has been a research hotspot in recent years and is gradually moving towards commercialization. According to the difference in the luminescence mechanism of luminescent materials, they can be divided into fluorescent materials and phosphorescent materials.

[0003] Human beings first came into contact with organic electroluminescence (EL) in 1936, when the Destriau team incorporated fluorescent organic compounds into polymers and made a film that could emit light under power conditions, but it did not attract people's attention at the time. In the following half century, due to a series of device defects such as large thickness, high starting voltage, low external quantum efficiency, low brightness, and mismatched materials for preparing devices, it was not possible to produce eye-catching devices, making the development of organic electroluminescent materials very slow. It was not until 1987 that Deng Qingyun's team used vacuum evaporation technology for the first time to use 8-hydroxyquinoline aluminum as both a luminescent material and an electron transport material to make a double-layer organic electroluminescent display device, opening up a new direction for organic electroluminescence. In 1998, Forrest et al. prepared devices using phosphorescent materials for the first time, and developed a green light device with an internal quantum efficiency of nearly 100% in 2001. This inspired the passion of scientific researchers and has since promoted the rapid development of the OLED industry. In 2009, Adachi's research group at Kyushu University in Japan applied porphyrin complexes of tin difluoride to OLED devices. This was the first application of TADF materials in electroluminescence, which opened up a research boom in TADF materials and their devices. Currently, TADF materials have made major breakthroughs from blue light to near-infrared regions. The TADF process is due to the energy level difference (ΔE) between the lowest excited singlet state and the lowest excited triplet state. ST ) is small enough that the triplet excitons are converted to singlet states through reverse intersystem crossing (RISC) after being heated, and the singlet excitons reradiate back to the ground state to emit light. Therefore, the internal quantum efficiency of devices based on TADF materials can theoretically reach 100%. Fast reverse intersystem crossing (RISC) is the key to obtaining high-efficiency TADF materials. Therefore, TADF materials usually need to exhibit a very small energy splitting (ΔE) between the excited singlet state (S1) and triplet state (T1). ST). To achieve this goal, the most widely used molecular design is to have a distorted donor (D)-acceptor (A) structure to effectively reduce the spatial overlap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO), thereby reducing ΔE ST .

[0004] In recent years, the research on the use of cross-linking groups in OLED device materials has received widespread attention at home and abroad. Among them, vinyl groups and oxetane groups are representative groups for thermal cross-linking and photocross-linking. Vinyl groups can undergo polymerization reactions at relatively low curing temperatures and without the need for initiators to form solvent-resistant films, and there are no by-products. Due to these advantages, vinyl groups have almost become the most commonly used cross-linking groups in cross-linking materials. At present, most of the research on the use of cross-linking materials in OLED devices focuses on hole transport materials and electron transport materials, while there are fewer studies on directly modifying them on light-emitting layer materials. Summary of the invention

[0005] The present invention constructs a thermally cross-linked fluorescent material based on vinyl groups, with 3-vinyl carbazole as the donor unit and 3,3'-bipyridine as the acceptor unit to construct the main material; 4-vinyl diphenylamine as the donor unit and bis(phenylsulfonyl)benzene as the acceptor unit to construct the guest material. At the same time, the influence of the photophysical properties of the material before and after cross-linking is studied, which is of great significance for exploring high-efficiency fluorescent materials.

[0006] In order to achieve the above technical purpose, the present invention provides a guest fluorescent material compound 1 constructed with 4-vinyldiphenylamine as a donor unit and bis(phenylsulfonyl)benzene as an acceptor unit; a fluorescent material compound 2 constructed with 3-vinylcarbazole as a donor unit and 3,3'-bipyridine as an acceptor unit as a host fluorescent material, having the following structure:

[0007]

[0008] Bis(phenylsulfonyl)benzene and 3,3'-bipyridine groups are used as acceptor units, donor units are introduced at their ortho positions, and different cross-linked donor units are changed to adjust the energy level difference between the singlet and triplet states of the molecule, making it easy to obtain TADF materials.

[0009] Another object of the present invention is to provide the use of compound 2 as a main material in the preparation of a solution-processed yellow light-emitting organic electroluminescent diode light-emitting layer, so as to obtain an organic electroluminescent device with excellent yellow light emission performance.

[0010] Furthermore, the thermally cross-linked fluorescent material compound 2 based on vinyl groups is doped with a guest material for use.

[0011] Furthermore, the thermally cross-linked fluorescent material compound 2 based on vinyl group is doped with the thermally cross-linked fluorescent material guest material compound 1 based on vinyl group, and the doping amount of the compound 1 is 1 wt.% to 5 wt.%.

[0012] More specifically, the method for preparing the organic electroluminescent diode light-emitting layer is as follows: dissolving the host material and the guest material in a chlorobenzene solution, spin coating the material on the surface of the hole injection layer, annealing the material, and heating and cross-linking the material to form the organic electroluminescent diode light-emitting layer.

[0013] Furthermore, the spin coating speed is 1500-1800 r / s, preferably 1700 r / s.

[0014] Further, the spin coating thickness is 54-56 nm, preferably 55 nm.

[0015] Furthermore, the annealing temperature is 70-90° C., preferably 80° C., and the annealing time is 15 min.

[0016] Furthermore, the temperature of the heating cross-linking reaction is 150-180° C., preferably 150° C., and the reaction time is 30 min.

[0017] Molecular cross-linking reaction process of compound 1 and compound 2:

[0018]

[0019] Compared with the prior art, the technical principle and beneficial effects of the present invention are:

[0020] (1) 1,3-vinylcarbazole and 4-vinyldiphenylamine are weak electron-donating units, while bis(phenylsulfonyl)benzene and 3,3'-bipyridine are strong acceptor units. The combination of the two is conducive to the separation of HOMO and LUMO orbitals, further reducing ΔE ST , making it easier to obtain TADF materials. Adding vinyl functional groups to the symmetric donor units further reduces the crosslinking temperature.

[0021] (2) Cross-linking groups are introduced into the molecule to form a three-dimensional network polymer after cross-linking. After cross-linking, the light-emitting layer has the characteristics of solvent resistance and thermal stability, which can prevent the light-emitting layer from being miscible with other layers, so that the light-emitting layer of OLED can be prepared by solution processing. This is of great significance for solving the problem of corrosion of the upper layer solvent to the lower layer film during multi-layer solution preparation, and is conducive to the industrial production of large-scale OLED device preparation.

[0022] (3) The present invention obtains a series of thermally cross-linked fluorescent materials, whose electroluminescent emission wavelength is in the yellow light region.

[0023] (4) The present invention obtains a TADF-OLED device with yellow electroluminescent color. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The thermal gravimetric curves of Compound 1 and Compound 2 prepared in Example 1 of the present invention;

[0025] Figure 2 The differential scanning calorimetry spectra of compound 1 (A) and compound 2 (B) prepared in Example 1 of the present invention are shown;

[0026] Figure 3 The UV-visible light absorption and photoluminescence spectra of Compound 1 (A) and Compound 2 (B) prepared in Example 1 of the present invention in toluene solution;

[0027] Figure 4 The low temperature (77K) fluorescence and phosphorescence spectra of compound 1 (A) and compound 2 (B) obtained in Example 1 of the present invention in toluene solution are shown;

[0028] Figure 5 The photoluminescence spectra of compound 1 (A) and compound 2 (B) prepared in Example 1 of the present invention in petroleum ether, n-hexane, tetrahydrofuran, dichloromethane, chloroform, toluene, acetonitrile and N,N-dimethylformamide;

[0029] Figure 6 The instantaneous life curve of compound 1 (A) and compound 2 (B) prepared in Example 1 of the present invention in toluene solution;

[0030] Figure 7 The instantaneous life curve of compound 2 prepared in Example 1 of the present invention in a 5% doped compound 1 film (A); and the delayed life curve (B);

[0031] Figure 8 The electroluminescence spectra of the compound 2 prepared in Example 1 of the present invention as the main material and doped with 1wt.% and 5wt.% of the compound 1 as the guest;

[0032] Fig. 9 This is a relationship diagram of the maximum external quantum efficiency of compound 2 prepared in Example 1 of the present invention as the main material and doped with 1wt.% and 5wt.% of compound 1 as the guest. DETAILED DESCRIPTION

[0033] The following specific implementation cases are intended to further illustrate the present invention, but these specific implementation cases do not limit the protection scope of the present invention in any way.

[0034] Example 1

[0035] The synthesis scheme of the thermally cross-linked thermally activated delayed fluorescent material compound 1 based on vinyl groups is as follows:

[0036]

[0037] Synthesis of compound SM1

[0038] Thiophenol (3.00 g, 27.23 mmol) and 1,5-dibromo-2,4-difluorobenzene (2.96 g, 10.89 mmol) were dissolved in 1,4-dioxane (40 ml), and the solution was heated. When the solution temperature reached 110 ° C, cuprous iodide (3.11 g, 16.34 mmol) and potassium phosphate (23.12 g, 108.91 mmol) were added to the solution. After reflux, trans-1,2-cyclohexane (1.96 ml, 16.34 mmol) was added to the solution. The solution was stirred for 2 days under a nitrogen atmosphere and then cooled to room temperature. After filtering the solution to remove potassium phosphate, the solution was dried and extracted with dichloromethane and distilled water. The product dissolved in dichloromethane was dehydrated with anhydrous MgSO4. The crude product was purified by column chromatography using an eluent (dichloromethane:n-hexane=1:10) to obtain the target compound as a white powder (4.31 g) with a yield of 47.9%. 1 HNMR (400MHz, d6-DMSO) δ (ppm) 7.43 (d, J = 4.3Hz, 10H), 7.07 (t, J = 7.7Hz, 2H).

[0039] Add (2,5-difluoro-1,4-phenyl)bis(phenylsulfane) (4.31 g, 13.1 mmol) and 60 mL of glacial acetic acid to a 200 mL single-mouth bottle, add 30 mL of hydrogen peroxide dropwise while stirring, heat to 100 ° C and reflux for 24 hours. Cool to room temperature, pour the mixture into 100 mL of water, and a white solid precipitates. Filter, collect the solid, dry, and recrystallize with ethanol to obtain 3.1 g of the target compound as a white solid with a yield of 59%. 1 HNMR (400MHz, CDCl3) δ (ppm) 7.98 (t, J = 9.5 Hz, 4H), 7.86 (t, J = 6.6 Hz, 2H), 7.69 (t, J = 7.5 Hz, 2H), 7.58 (t, J = 7.8 Hz, 4H).

[0040] Synthesis of compound SM2

[0041] Aniline (2.44 g, 26.2 mmol), p-bromostyrene (4.00 g, 21.80 mmol), tris(dibenzylideneacetone)dipalladium(0) (489.00 mg, 4.90 mmol), bis(diphenylphosphino)ferrocenepalladium dichloride (599.00 mg, 0.65 mmol), sodium tert-butoxide (6.90 g, 123.60 mmol), and 50 mL of toluene were added in sequence to a 200 mL single-mouth bottle, and the mixture was heated to 120° C. and refluxed for 24 hours under nitrogen protection. The mixture was cooled to room temperature, filtered, washed with dichloromethane, the filtrate was collected, the solvent was dried, extracted with dichloromethane (3×40 mL), washed with water three times, dried over anhydrous magnesium sulfate, filtered, the filtrate was collected, the solvent was dried, and the target compound (3.48 g) was separated by column chromatography using petroleum ether as the eluent as a light yellow flaky solid with a yield of 81%. 1 HNMR(400MHz,d6-DMSO)δ(ppm)8.28(s,1H),7.33(d,J=7.9Hz,2H),7.23(d,J=7.4Hz,2H),7.09(s,2H), 7.03(d,J=7.9Hz,2H),6.84(s,1H),6.67–6.53(m,1H),5.61(d,J=17.6Hz,1H),5.05(d,J=10.8Hz,1H).

[0042] Synthesis of compound 1

[0043] The following raw materials were added to a 100mL two-necked flask: SM1 (1.00g, 2.54mmol), SM2 (1.09g, 5.58mmol) and 60% sodium hydride (203.00mg, 5.07mmol). After nitrogen protection, 25mL of DMF was added to the system with a syringe, and refluxed at 120℃ for 18h. After the reaction was completed, it was cooled to room temperature, and water was added to filter and dry the filter cake. Petroleum ether and dichloromethane (volume ratio 3:2) were used as eluents, and column chromatography was performed to obtain 1.4g of yellow solid powder with a yield of 74%. 1 HNMR (400MHz, CDCl3) δ (ppm) 8.08 (s, 2H), 7.44 (t, J = 7.3Hz, 2H), 7.37 (d, J = 7.8Hz, 4H), 7.21 (dd, J = 16.5, 6.9Hz, 5H), 7.18–7 .12(m,7H),7.02(t,J=7.2Hz,2H),6.78(d,J=7.6Hz,4H),6.67–6.57(m,6H),5.63(d,J=17.7Hz,2H),5.19(d,J=10.9Hz,2H).

[0044] The synthesis scheme of the fluorescent material compound 2 based on vinyl group is as follows:

[0045]

[0046] Synthesis of compound SM3

[0047] In a 200mL single-mouth bottle, add 2-fluoro-3-pyridineboronic acid (4.78g, 34.10mmol), 3-bromo-2-fluoropyridine (5.00g, 28.40mmol), tetrakis(triphenylphosphine)palladium (1.97g, 1.97mmol), 20mL of 2mol / L sodium hydroxide aqueous solution, 20mL of analytically pure tetrahydrofuran and 6mL of distilled water (volume ratio 3:1) in sequence. Protect with nitrogen and reflux at 80℃ for 24h. After the reaction is completed, cool to room temperature, spin dry the solvent, add water and extract with dichloromethane, wash with water three times, filter and collect the filtrate, spin dry the solvent. Use petroleum ether and dichloromethane (volume ratio 1:1) as eluents, separate by column chromatography to obtain 2.3g of white solid, with a yield of 38.7%. 1 HNMR (400MHz, DMSO) δ8.37 (d, J = 4.4Hz, 2H), 8.17 (dd, J = 11.0, 5.5Hz, 2H), 7.58–7.52 (m, 2H).

[0048] Synthesis of compound SM4

[0049] The following raw materials were added to a 100mL two-necked flask: SM3 (1.00g, 2.54mmol), 3-bromocarbazole (1.09g, 5.58mmol) and 60% sodium hydride (203.00mg, 5.07mmol). After nitrogen protection, 25mL of DMF was added to the system with a syringe, and refluxed at 120℃ for 18h. After the reaction was completed, it was cooled to room temperature, and the filter cake was dried after filtration with water. Petroleum ether and dichloromethane (volume ratio 3:2) were used as eluents, and 1.4g of white solid was obtained by column chromatography, with a yield of 74%. 1 H NMR (400MHz, CDCl3) δ8.52 (s, 2H), 8.29 (s, 2H), 7.62 (d, J = 29.0Hz, 6H), 7.01 (d, J = 32.7Hz, 6H), 6.54–5.93 (m, 4H).

[0050] Synthesis of compound 2

[0051] Compound SM4 (1.20 g, 1.86 mmol), vinylboronic acid pinacol ester (0.63 g, 4.10 mmol), tetrakis(triphenylphosphine)palladium (129.00 mg, 0.11 mmol), 10 mL of sodium hydroxide aqueous solution (2 mol / L), and 30 mL of tetrahydrofuran were added to a 100 mL single-mouth bottle in sequence, and the mixture was heated to 80 ° C under nitrogen protection and refluxed for 24 h. Cool to room temperature, spin dry the solvent, extract with dichloromethane (3×30 mL), wash three times with water, dry with anhydrous magnesium sulfate, filter, collect the filtrate, spin dry the solvent, and separate by column chromatography with petroleum ether: dichloromethane (2:3, v / v) as the eluent to obtain 0.68 g of white solid powder with a yield of 68%. 1 H NMR (400MHz, CDCl3) δ8.51(s,2H),8.30(s,2H),7.56(s,6H),6.90(s,6H),6. 74(s,2H),6.43–6.09(m,4H),5.66(d,J=17.7Hz,2H),5.15(d,J=10.5Hz,2H).

[0052] Example 2

[0053] Compound 1 and Compound 2 in Example 1 were heated at a rate of 20°C per minute in a N2 atmosphere within a range of 30 to 750°C, and thermogravimetric curves were measured. Figure 1 It can be seen that the 5% decomposition temperatures of Compound 1 and Compound 2 are 418.5°C and 445.3°C, respectively.

[0054] Example 3

[0055] The test was performed in N2 atmosphere at a rate of 10℃ / min by heating and cooling twice (25~350℃). Figure 2 It can be seen that the exothermic peaks of compound 1 in the first heating cycle are 204.3°C and 225.8°C, the endothermic peak is 228.6°C, and no endothermic peaks or exothermic peaks appear in the second heating cycle, indicating that compound 1 has completed the cross-linking process, recorded as cross-linked compound 1-J. The endothermic peak of compound 2 in the first heating cycle is 143.2°C, and no endothermic peak appears in the second heating cycle, indicating that compound 2 has completed cross-linking, recorded as cross-linked compound 2-J. According to the cross-linking exothermic peak of the DSC curve, the cross-linking temperature is determined to be 150-180°C.

[0056] Example 4

[0057] The compound 1 and compound 2 in Example 1 were dissolved in toluene to prepare 10 -5 M solution, and test its UV-visible absorption and photoluminescence spectrum. Figure 3It can be seen that the UV-visible absorption spectrum of compound 1 in solution has roughly two absorption peaks: the absorption peak at short wavelength (310nm) is mainly attributed to the transition absorption of π-π* of the molecule; the absorption peak at long wavelength (400-500nm) is attributed to the charge transfer (ICT) transition absorption peak from the donor unit to the acceptor unit in the molecule. In addition, under light excitation, the maximum emission peak of compound 1 is 595nm. The UV-visible absorption spectrum of compound 2 in solution has roughly two absorption peaks: the absorption peak at short wavelength (310nm) is mainly attributed to the transition absorption of π-π* of the molecule; the absorption peak at long wavelength (315-335nm) is attributed to the charge transfer (ICT) transition absorption peak from the donor unit to the acceptor unit in the molecule. In addition, under light excitation, the maximum emission peak of compound 2 is 455nm.

[0058] Example 5

[0059] The low temperature (77K) fluorescence and phosphorescence spectra of Compound 1 and Compound 2 in Example 1 were tested in toluene solution under nitrogen atmosphere. Figure 4 As shown in A, according to the starting peak positions of the low-temperature fluorescence and low-temperature phosphorescence spectra, the singlet and triplet energy levels of compound 1 are calculated to be 2.46 / 2.31 eV respectively according to the formula E=1240 / λ, and the singlet / triplet energy level difference is obtained to be 0.15 eV. Obviously, compound 1 has a relatively small single-triplet energy gap difference. Figure 4 As shown in Figure B, based on the starting peak positions of the low-temperature fluorescence and low-temperature phosphorescence spectra, the singlet and triplet energy levels of compound 2 are calculated to be 3.08 / 2.60 eV respectively according to the formula E=1240 / λ, and the singlet / triplet energy level difference is obtained to be 0.52 eV. Obviously, compound 2 has a relatively small single-triplet energy gap difference.

[0060] Example 6

[0061] The photoluminescence performance of compound 1 and compound 2 in Example 1 in different solutions was tested. Compound 1 or compound 2 was dissolved in petroleum ether, n-hexane, tetrahydrofuran, dichloromethane, chloroform, toluene, acetonitrile and N,N-dimethylformamide solution, and its photoluminescence spectrum in different solutions was tested. Figure 5 As shown in the figure, under light excitation, the emission wavelengths of compound 1 and compound 2 show a certain red shift as the polarity of the solvent increases, indicating that these compounds have strong intramolecular charge transfer.

[0062] Example 7

[0063] The fluorescence lifetime of compound 1 and compound 2 in Example 1 in toluene solution was tested under nitrogen atmosphere. Figure 6As shown, after fitting, the delayed lifetime of compound 1 was 2.85ns, which was a short lifetime; the delayed lifetime of compound 2 was 4.05ns, which was a short lifetime.

[0064] Example 8

[0065] The fluorescence lifetime of the film doped with 5 wt% of compound 1 in Example 1 in compound 2 was tested under nitrogen atmosphere using Edinburgh transient / steady-state spectrometer FLS1000 (with EPLED-365 as the light source). Figure 7 As shown in A, the delayed lifetime of the doped film is 3.97ns after fitting, which is a short lifetime.

[0066] The fluorescence lifetime of the film in which 5 wt % of compound 1 in Example 1 was doped in compound 2 was tested under nitrogen atmosphere using Edinburgh transient / steady-state spectrometer FLS1000 (the light source was a flash xenon lamp). Figure 7 As shown in B, the delayed lifetime of the doped film is 4.27 μs after fitting, which is a long lifetime.

[0067] Example 9

[0068] Application of compounds 1 and 2 in Example 1 in organic electroluminescent devices. An organic electroluminescent diode having a structure of ITO / PEDOT:PSS (40nm) / compound 2: (compound 1 1wt% or 5wt%) / DPEPO 9nm) / TmPyPB (45nm) / Liq (0.5nm) / Al (120nm) was prepared using compound 1 as a dopant in the light-emitting layer of the device. Among them, PEDOT:PSS is a hole injection layer, compound 2 is a main material of the light-emitting layer, DPEPO is a hole blocking layer, TmPyPB is an electron transport layer, and Liq / Al is a cathode.

[0069] Cross-linked device preparation method:

[0070] 1. First, the indium tin oxide (ITO) substrate was ultrasonically cleaned according to the steps of isopropyl alcohol (20 min), acetone (20 min), ITO cleaning solution (10 min), deionized water (40 min), and isopropyl alcohol (20 min), dried in an oven at 80°C for 4 h, and the surface of the substrate was treated with ultraviolet ozone at 100°C for 15 min;

[0071] 2. Spin-coat a 1.5% PEDOT:PSS solution on the substrate at 3200 r / min for 30 s and anneal at 150 °C for 15 min in a nitrogen atmosphere;

[0072] 3. The preparation process of the luminescent layer is to add compound 1 at 1 wt% orThe mixture doped with the host compound 2 at a concentration of 5 wt% was dissolved in a chlorobenzene solution and spin-coated on the PEDOT:PSS injection layer at a speed of 1700 r / min to obtain a 55 nm thick film. After the coating, the substrate was annealed at 80 °C for 15 minutes to remove the residual solvent, and then heated at 150 °C for 30 minutes for cross-linking reaction;

[0073] 4. After annealing, DPEPO, TmPyPB, LiF, and Al are sequentially deposited on the light-emitting layer in the evaporation chamber to a predetermined thickness, wherein the evaporation rate of DPEPO is controlled at The evaporation rate of TmPyPB was controlled at The LiF evaporation rate is controlled at The Al evaporation rate is controlled at

[0074] 5. After the evaporation is completed, all devices are UV-cured and encapsulated with UV-curing glue and encapsulation sheets in the N2 atmosphere of the glove box, and then tested.

[0075] The electroluminescence spectrum of compound 1 in Example 1 in an organic electroluminescent device is as follows: Figure 8 As shown in the figure, the devices prepared under the two doping conditions of 1wt% and 5wt% showed yellow light emission, and the emission peak was 560nm. After cross-linking, the devices with 1wt.% and 5wt.% of compound 1 doped in compound 2 obtained maximum external quantum efficiencies of 1.13% and 1.23%, respectively, and the color coordinates were (0.34, 0.41) and (0.42, 0.48), as shown in the figure. Fig. 9 shown.

[0076] During the device preparation process, cross-linked luminescent materials need to be annealed and heated for cross-linking at high temperatures. The cross-linking temperature is usually higher than 80°C. If other host materials or guest materials selected cannot withstand high temperatures above 80°C, crystallization will occur during the device preparation process.

[0077] Although the present invention has been described in conjunction with the preferred embodiments, the present invention is not limited to the above embodiments, and it should be understood that the appended claims summarize the scope of the present invention. Under the guidance of the inventive concept, those skilled in the art should be aware that certain changes made to the various embodiments of the present invention will be covered by the spirit and scope of the claims of the present invention.

Claims

1. A thermally cross-linked fluorescent material based on vinyl groups, characterized in that: The molecular structural formula of the thermally cross-linked fluorescent material based on vinyl groups is shown in Formula I and Formula II; the compound of Formula I and the compound of Formula II are doped and used for solution processing to prepare the light-emitting layer of an organic electroluminescent diode; Wherein the compound of formula I is used as the host material, and the compound of formula II is used as the guest material; , Formula I, , Formula II.

2. The use of the thermally cross-linked fluorescent material based on vinyl groups according to claim 1, characterized in that: The compound of formula I is used as a main material and the compound of formula II is doped as a guest material in the preparation of an organic electroluminescent diode light-emitting layer by solution processing.

3. The use of the thermally cross-linked fluorescent material based on vinyl groups according to claim 2, characterized in that: The organic light emitting diode light emitting layer emits yellow light.

4. The use of the thermally cross-linked fluorescent material based on vinyl groups according to claim 2, characterized in that: The preparation method of the light-emitting layer is as follows: dissolving the main material and the guest material in a chlorobenzene solution, spin coating on the surface of the hole injection layer, annealing, heating and cross-linking to form an organic electroluminescent diode light-emitting layer.

5. The use of the thermally cross-linked fluorescent material based on vinyl groups according to claim 4, characterized in that: The spin coating speed is 1500-1800 r / s.

6. The use of the thermally cross-linked fluorescent material based on vinyl groups according to claim 4, characterized in that: The spin coating thickness was 54-56 nm.

7. The use of the thermally cross-linked fluorescent material based on vinyl groups according to claim 4, characterized in that: The annealing temperature is 70-90°C and the annealing time is 15 min.

8. The use of the thermally cross-linked fluorescent material based on vinyl groups according to claim 4, characterized in that: The temperature of the heating cross-linking reaction is 150-180°C, and the reaction time is 30 min.

Citation Information

Patent Citations

  • Crosslinkable host materials

    CN106715420A